Коммуникативный перенос в поэзии А. Межирова - Шульская, О. В. (Kalbotyra, 1994)
The device of commutation, modes of persons switching in the lyric work are investigated in the article. These peculiarities of poetics are presented in the context of perseptinion of the world typical for Mejirov.